2013
DOI: 10.1016/j.ijproman.2012.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Obsessive passion, competence, and performance in a project management context

Abstract: Obsessive passion is when people have a strong inclination toward an activity that they like, find important, and in which they spend significant time, but also feel internal pressure to engage in.Prior research has demonstrated that obsessive passion typically brings several negative consequences. The present study nuances the picture by showing that there are indeed conditions when obsessive passion can be beneficial and that it has an important role for project management. It develops and tests hypotheses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 99 publications
0
18
0
Order By: Relevance
“…It is noteworthy that recent empirical research has shown the positive 'face' of the 'dark side' of passion (Patel et al, 2015;Omorede, Thorgren, & Wincent, 2013), proposing that leaders who score high in obsessive passion are likely to excel in highly dynamic environments. If one accepts that management of football occurs in a setting characterized by high degree of unpredictability and uncertainty (Hamil & Chadwick, 2010), then having obsessively passionate employees may lead to better organisational performance.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that recent empirical research has shown the positive 'face' of the 'dark side' of passion (Patel et al, 2015;Omorede, Thorgren, & Wincent, 2013), proposing that leaders who score high in obsessive passion are likely to excel in highly dynamic environments. If one accepts that management of football occurs in a setting characterized by high degree of unpredictability and uncertainty (Hamil & Chadwick, 2010), then having obsessively passionate employees may lead to better organisational performance.…”
Section: Discussionmentioning
confidence: 99%
“…In the entrepreneurship and management research, some studies build on the DMP (e.g., Ho, Wong, and Lee, 2011;Klaukien, Shepherd, and Patzelt, 2013;Thorgren and Wincent, in press;Omorede, Thorgren, and Wincent, 2013), whereas other studies draw rather on more context specific works, such as Baum and Locke (2004) and Cardon et al's (2009) conceptual framework on entrepreneurial passion (Cardon, Gregoire, Stevens, and Patel, 2013). However, regardless of the framework used, the extant research has focused on examining variance in the extent of experienced passion and its outcomes.…”
Section: Theoretical Framework and Hypothesis Developmentmentioning
confidence: 99%
“…The concept of passion has a long history in both research and practice, yet only in the past decade has it gained extensive scholarly attention and development following the work of Vallerand and colleagues' (2003) Dualistic Model of Passion (e.g., Amiot, Vallerand, & Blanchard, 2006;Mageau, Vallerand, Rousseau, Ratelle, & Provencher, 2005;Omorede, Thorgren, & Wincent, 2013;Ratelle, Vallerand, Mageau, Rousseau, & Provencher, 2004;Vallerand & Houlfort, 2003). In this model, passion is defi ned as "a strong inclination or desire toward an activity that one likes, fi nds important, and in which one invests time and energy" (Vallerand et al, 2003, p. 757).…”
Section: Introductionmentioning
confidence: 99%